The Effect of Budget Efficiency Policies on Employment in West Java’s Hospitality Sector: A Case Study on Hotel and Restaurant Layoffs - Ahyani, Hisam; Kuncoro, Irfan; Sartono, Sartono; Hidayat, Moh. Syarif; Abduloh, Agus Yosep (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
This study examines the impact of budget efficiency policies on labor in the hospitality industry in West Java, focusing on employee reductions in hotels and restaurants. In 2025, the Indonesian government's budget cuts aimed at reducing the fiscal deficit severely impacted the hospitality sector, which relies on government-funded activities like seminars and official travel. Using interviews and secondary data, the study found a sharp decline in hotel occupancy rates, leading to financial difficulties and an estimated 40,000 layoffs. The findings highlight the need for policy adjustments, including financial support for businesses and targeted recovery plans for SMEs, to ensure long-term stability in the region’s hospitality industry.